(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine the frequency of vitamin D deficiency in the patients of liver cirrhosis. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Department of Medicine, DHQ Hospital of MuzaffarGarh from August 2014 to September 2015. Materials and Methods: Every case of liver cirrhosis was made a part of this study after diagnosis. Severity of the cirrhosis was classified according to child Pugh classification. Severity of vitamin D deficiency was categorized as mild, moderate and severe. Vitamin D level was evaluated through blood sample of every case fromdiagnostic hospital Laboratory Results: In this study 100 patients were chosen. The number of male was appeared in majority71.0% and mean age was 46.7+7.2years. Mean of alanine aminotransferase was figured as 60+42U/L.HCV infection was the major etiological factor in 53.0% of the cases. Majority of the cases in Child-Pugh’s class 'A' 42%. Ascites was almost in all cases. Severe deficiency of the vitamin D was found significantly associated with Pugh grade C in37.5% cases, followed by 26.4% in grade B of and 21.5% in grade A of child Pugh. Conclusion: Deficiency of vitamin D in cirrhotic patients is big prevalent, and also associated with severity of the cirrhosis.